Sedentary Behaviour in Human Health and Disease - Daniel P. Bailey (Frontiers Research Topics, 2018)
Sedentary behaviour - too much sitting as distinct from too little physical activity - is now recognised as an independent risk factor for several health outcomes and premature mortality. This is problematic as technological advancements in transportation, communications, workplaces, and domestic entertainment has created environments that encourage engagement in sedentary behaviour. Evidence from observational epidemiology shows that prolonged sitting is associated with increased risk of disease and adverse risk marker levels including type 2 diabetes, cardiovascular diseases, some cancers, obesity, glucose tolerance, and lipids. Importantly, the associations between prolonged sitting and these health markers are independent of time spent in moderate-to-vigorous physical activity. Intriguingly, observational studies employing objective measures of sedentary time patterns using accelerometry have shown that adults who interrupt their sedentary time more frequently (breaks in sedentary time) have improved cardiometabolic profiles than those whose sedentary time is mostly uninterrupted. These beneficial associations are independent of total sedentary time and time spent in moderate-to-vigorous physical activity. In light of this evidence, experimental studies are now being conducted to identify novel mechanisms and potential causal relationships. It has been suggested that loss of muscular contractile stimulation induced through sitting impairs skeletal muscle metabolism of lipids and glucose and that the molecular processes through which these responses occur may be separate from the pathways activated when engaging in exercise. This Research Topic aims to bring together contributions from researchers to advance the sedentary behaviour research agenda and strengthen the case for reducing and breaking up sitting time in primary prevention and disease management contexts.